Corneal Ectasia After Keratorefractive Surgery: High-Order Aberration Management and Hormonal Considerations - Supit, Fabiola; Handayani, Ariesanti Tri (Vision Science and Eye Health Journal, 2026)
Introduction: To report a case of corneal ectasia after corneal refractive surgery successfully treated with a corneal rigid gas permeable (RGP) contact lens. Case Presentation: A 30-year-old woman presented with blurred vision and significant glare six months after bilateral refractive lenticule extraction–small incision lenticule extraction (ReLEx SMILE) surgery. The spectacle prescription showed inconsistent results. Corneal topography revealed increased high-order aberration (HOA) with values of 4.470/19.742 in the right eye and 2.543/9.931 in the left eye. After RGP lens fitting, HOA significantly improved to 0.921/1.746 in the right eye and 0.501/0.814 in the left eye, accompanied by marked improvement in subjective visual. However, after three months of follow-up, the patient experienced worsening visual symptoms and topographic findings in the left eye. Conclusions: RGP lenses do not prevent progression but can correct impaired visual function due to ectasia after corneal refractive surgery. Stricter patient selection, including consideration of hormonal factors affecting the eye, is needed to minimize the risk of keratorefractive ectasia.